2020
DOI: 10.1038/s41598-020-68845-y
|View full text |Cite
|
Sign up to set email alerts
|

Response of spike-wave discharges in aged APP/PS1 Alzheimer model mice to antiepileptic, metabolic and cholinergic drugs

Abstract: Epileptic nonconvulsive spike-wave discharges (SWDs) are commonly seen in amyloid plaque bearing transgenic mice but only rarely in their wild-type littermates. To shed light on their possible treatment options, we assessed the effect of drugs with variable and known mechanisms of action on the occurrence of SWDs in aged APPswe/PS1dE9 mice. The treatments included prototypic antiepileptic drugs (ethosuximide and levetiracetam), donepezil as the typical Alzheimer drug and atropine as an antagonistic effect, GAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…While these findings for seizure worsening with high dose administration of sodium channel blocking ASDs is at first glance concerning for a mouse model of AD, it is well established that sodium channel blockers can lower seizure threshold at high doses [ 76 , 79 ], thus care should be taken to not over interpret these findings as specific to AD models. Lastly, Jin and colleagues have also more recently demonstrated an effect of ESM (200 mg/kg) and LEV (75 mg/kg) on state-dependent spike-wave discharges (SWDs) in aged APP/PS1 mice [ 80 ]. This study highlights the capacity to evaluate the efficacy of ASDs on specific types of epileptiform activity that is also observed in genetically susceptible rat models of absence epilepsy [ 57 , 81 , 82 ].…”
Section: Preclinical Models Of Aging and Epilepsy Should Address Clinical Needsmentioning
confidence: 99%
“…While these findings for seizure worsening with high dose administration of sodium channel blocking ASDs is at first glance concerning for a mouse model of AD, it is well established that sodium channel blockers can lower seizure threshold at high doses [ 76 , 79 ], thus care should be taken to not over interpret these findings as specific to AD models. Lastly, Jin and colleagues have also more recently demonstrated an effect of ESM (200 mg/kg) and LEV (75 mg/kg) on state-dependent spike-wave discharges (SWDs) in aged APP/PS1 mice [ 80 ]. This study highlights the capacity to evaluate the efficacy of ASDs on specific types of epileptiform activity that is also observed in genetically susceptible rat models of absence epilepsy [ 57 , 81 , 82 ].…”
Section: Preclinical Models Of Aging and Epilepsy Should Address Clinical Needsmentioning
confidence: 99%
“…In contrast, donepezil, a cholinesterase inhibitor had no significant effect on interictal spikes ( 122 ). Another study using the APPswe/PS1dE9 mouse model presenting with spike–wave discharges (SWDs), showed that donepezil does not have a significant effect on epileptic activity whereas atropine decreases SWDs and results in EEG slowing ( 123 ). This information suggests that before the degeneration of cholinergic neurons in AD and DLB, there could be a phase of increased cholinergic tone that contributes to an increase in neuronal activity and epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…We have found that an increase in the cortical excitability induced by injection of physostigmine, a reversible cholinesterase inhibitor which increases the ACh level in the brain, increased the frequency of epileptiform-like discharges in APP/PS1 mice 40 . Accordingly, atropine, a muscarinic cholinergic receptor antagonist, significantly decreased epileptiform-like discharge occurrence in APP/PS1 mice 69 .…”
Section: Eeg Studies In Admentioning
confidence: 91%